Ecosystem Under Construction – An Action Research Study on Entrepreneurship in a Business Ecosystem - Marikka Heikkilä; Leni Kuivaniemi (My University, 2022)
In recent years, we have seen increasing interest in new service concepts that take advantage of the capabilities of business ecosystems instead of single companies. In this article, we describe how a business ecosystem begins to develop around a service business idea proposed by an entrepreneur. We aim to recognize the different domains of players that are or should be involved in the ecosystem while it is under construction. The article concludes with an ecosystem model consisting of six sub-ecosystems having different change drivers and clockspeeds. - See more at: http://timreview.ca/article/564#sthash.HWHQ64Oc.dpuf